Caveolar Endocytosis Is Required for Human PSGL-1-Mediated Enterovirus 71 Infection - Lin, Hsiang-Yin (American Society for Microbiology, 2013)
Enterovirus 71 (EV71) causes hand, foot, and mouth disease and severe neurological disorders in children. Human scavenger receptor class B member 2 (hSCARB2) and P-selectin glycoprotein ligand-1 (PSGL-1) are identified as receptors for EV71. The underling mechanism of PSGL-1-mediated EV71 entry remains unclear. The endocytosis required for EV71 entry were investigated in Jurkat T and mouse L929 cells constitutively expressing human PSGL-1 (PSGL-1-L929) or human rhabdomyosarcoma (RD) cells displaying high SCARB2 but no PSGL-1 by treatment of specific inhibitors or siRNA. We found that disruption of clathrin-dependent endocytosis prevented EV71 infection in RD cells, while there was no influence in Jurkat T and PSGL-1-L929 cells. Disturbing caveolar endocytosis by specific inhibitor or caveolin-1 siRNA in Jurkat T and PSGL-1-L929 cells significantly blocked EV71 infection, whereas it had no effect on EV71 infection in RD cells. Confocal immunofluorescence demonstrated caveola, and EV71 was directly colocalized. pH-dependent endosomal acidification and intact membrane cholesterol were important for EV71 infection, as judged by the pretreatment of inhibitors that abrogated the infection. A receptor-dominated endocytosis of EV71 infection was observed: PSGL-1 initiates caveola-dependent endocytosis and hSCARB2 activates clathrin-dependent endocytosis.